TINJAUAN INTEGRATIF STUDI DIFUSI INOVASI TEKNOLOGI PENDIDIKAN DI SEKOLAH - Suyantiningsih Suyantiningsih (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Our educational systems nowadays are facing inordinate difficulties in trying to meet the needs of a changing and increasingly technological society. However, there are many uncertainties related to the benefits of technology utilisation and development and the changes that the adoption of technology necessitates, such as demand for technical and non-technical supports, pedagogical and instructional issues, instuctional management issues, and teacher professional development. This article discusses three components of diffussion innovation in general concept. The first component includes characteristics of the innovation itself. A second component involves the characteristics of innovators (actors) that influence the probability of adoption of an innovation. The third component involves characteristics of the environmental context that modulate diffusion via structural characteristics of the modern world. These latter characteristics incorporate four sets of variables: geographical settings, societal culture, political conditions, and global uniformity. This article also presents a diverse set of literature in the area of